2018
DOI: 10.1021/acs.est.8b06457
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNAs Associated with Arsenic Exposure

Abstract: Arsenic (As) is a toxic metalloid. Inorganic arsenic (iAs) is a form of As commonly found in drinking water and in some foods. Overwhelming evidence suggest that people chronically exposed to iAs are at risk of developing cancer, or cardiovascular, neurological and metabolic diseases. Although the mechanisms underlying iAs-associated illness remain poorly characterized, a growing body of literature raises the possibility that microRNAs (miRNAs), post-transcriptional gene suppressors, may serve as mediators and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 99 publications
0
21
0
Order By: Relevance
“…(n=109) demonstrated significant correlations of plasma MMA with six circulating miRNAs including two linked to cardiovascular disease and diabetes (i.e. miRs-423-5p, −454-5p) although plasma iAs or DMA did not show any association (Beck et al, 2018). A study of 6-12 year old children in North Central Mexico indicated associations of total UAs and monomethylated arsenicals with decreased expression levels of Tumor Necrosis Factor-(TNF)-regulated immune and inflammatory response proteins (Smeester et al, 2017).…”
Section: Genotoxicity Cytotoxicity and Other Biochemical Effectsmentioning
confidence: 98%
“…(n=109) demonstrated significant correlations of plasma MMA with six circulating miRNAs including two linked to cardiovascular disease and diabetes (i.e. miRs-423-5p, −454-5p) although plasma iAs or DMA did not show any association (Beck et al, 2018). A study of 6-12 year old children in North Central Mexico indicated associations of total UAs and monomethylated arsenicals with decreased expression levels of Tumor Necrosis Factor-(TNF)-regulated immune and inflammatory response proteins (Smeester et al, 2017).…”
Section: Genotoxicity Cytotoxicity and Other Biochemical Effectsmentioning
confidence: 98%
“…Ruiz-Vera et al [93] have demonstrated an alteration in the expression levels of two miRNAs (miR-155 and miR-126) associated with cardiovascular disease in women in Mexico exposed to iAs via drinking water. Similarly, high iAs exposure was associated with altered profiles of circulating miRNAs in plasma of healthy subjects from Mexico, and four of the identified miRNAs (miR-423-5p, -423-5p +1, -142-5p -2, and -454-5p) appear to be linked to a risk of cardiometabolic diseases [94]. In a study that investigated the health impacts from prenatal exposure ranging up to 236.0 µg As/L in drinking water in Mexico, researchers found a set of differently expressed miRNAs and mRNAs that were implicated in innate and adaptive immune response [95].…”
Section: Arsenic-associated Changes In Mirna Expressionmentioning
confidence: 94%
“…One such study, published in 2006, for the rst time demonstrated that 2 µM/l sodium arsenite exposure for 6 days to human lymphoblastoid cells (TK-6) led to altered miRNA expression pro les (Marsit et al 2006). Recently, various cohort studies have determined alterations in miRNA expression levels in circulating uids of human populations exposed to signi cantly high levels of arsenic ( Sun et al, 2017;Beck et al, 2018;Ruíz-Vera et al, 2019;Zeng et al, 2019). Some works have focused on miRNA mediated growth inhibiting and apoptosis-inducing properties of arsenic trioxide (As 2 O 3 ) and its use as therapeutic agent in treatment of leukemia (Gao et al 2010;Li et al 2010).…”
Section: Dna Methylation and Histone Modi Cationmentioning
confidence: 99%